2000
DOI: 10.1177/0146167200267010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Forced Exposure to a Hypothetical Population on False Consensus

Abstract: Participants were forced to view a hypothetical population of 30 bogus students. Later, participants estimated consensus for 10 traits in this predefined population. On the false consensus effect (FCE) measure (estimates from those who exemplify the trait contrasted with estimates from those who do not), false consensus was observed. On the accuracy measure (estimates compared with actual consensus), estimates regressed inward. A week delay between the forced viewing and consensus estimates enhanced the regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In the laboratory, suppression is induced by making participants understand that their self-referent knowledge is irrelevant for the predictions at hand. Then, residual correlations between self and prediction can be attributed to incomplete suppression (Kulig, 2000). One study showed how selfreferent knowledge can intrude into predictions regarding other people's consensus estimates (Krueger & Zeiger, 1993).…”
Section: Suppressionmentioning
confidence: 99%
“…In the laboratory, suppression is induced by making participants understand that their self-referent knowledge is irrelevant for the predictions at hand. Then, residual correlations between self and prediction can be attributed to incomplete suppression (Kulig, 2000). One study showed how selfreferent knowledge can intrude into predictions regarding other people's consensus estimates (Krueger & Zeiger, 1993).…”
Section: Suppressionmentioning
confidence: 99%
“…False consensus is also indexed through accuracy of perception (Kulig, 2000). Here, participants' estimates of the prevalence of an attitude or behavior are compared with its actual prevalence in the community, estimated from sample data.…”
mentioning
confidence: 99%
“…Interestingly, people are quite accurate at estimating community norms when given information on the entire population, but even under those circumstances have been found to show a small false consensus effect (Kulig, 2000). This means that selective exposure, which is the most common cognitive explanation for the false consensus effect, cannot fully explain the false consensus effect.…”
mentioning
confidence: 99%
“…This regression effect was proposed by Mullen and Hu (), and discussed in detail by de la Haye (). Its effect has been called a ‘contraction bias’ in psycho‐physical research (Poulton, ; chapter 7) and Kulig () induced the regression effect in an experimental version of a false consensus paradigm. For these reasons, consensus effects are best studied in a between‐subjects paradigm, which does not suffer from regression effects.…”
mentioning
confidence: 99%